TEMPOROMANDIBULAR DISORDERS: IMPACT ON QUALITY OF LIFE AND SLEEP IN DENTISTRY STUDENTS : disfunção temporomandibular: impacto na qualidade de vida e do sono em estudantes de odontologia - Priscilla Kelly Batista da Silva Leite Montenegro; Maria Paula Carneiro de Brito Oliveira; Robinsom Viegas Montenegro; Matheus Andrews dos Santos; Marcos André Azevedo da Silva; Amanda Lira Rufino de Lucena (Revista de Ciências da Saúde Nova Esperança, 2026)
Temporomandibular disorder (TMD) has a significant impact on individuals’ quality of life, leading to functional limitations and, consequently, psychosocial issues. In this context, self-perception of oral health-related quality of life (OHRQoL) becomes crucial in understanding the limitations and suffering of individuals affected by these conditions. This cross-sectional study, with both quantitative and qualitative approaches, evaluated how temporomandibular disorder negatively affects the OHRQoL and sleep quality of dentistry students at Faculdades de Enfermagem Nova Esperança (FACENE). The sample consisted of 66 students, assessed through three questionnaires: initially, the presence and severity of TMD were determined using Fonseca’s Anamnestic Index (FAI); the abbreviated version of the OHIP-14 questionnaire was used to assess OHRQoL, and the Pittsburgh Sleep Quality Index (PSQI) was applied to analyze sleep quality. Data were processed using the SPSS software version 28 (Statistical Package for the Social Sciences) and analyzed through the chi-square test. It was identified that 65.1% of participants had at least some degree of TMD, with 34.8% (n=23) classified as mild, 25.8% (n=17) as moderate, and 4.5% (n=3) as severe, while 34.8% showed no symptoms of TMD. Results from the OHIP-14 questionnaire indicated the greatest impact on quality of life in the domains related to psychological discomfort (1.23), physical pain (1.14), and psychological disability (1.0). Regarding sleep quality, among students with moderate or severe TMD, 25% had good sleep quality, 42% had poor sleep quality, and 33% experienced sleep disturbances. These findings demonstrate that TMD has a negative impact on the quality of life and sleep of dentistry students.